2010
DOI: 10.1124/jpet.110.169995
|View full text |Cite
|
Sign up to set email alerts
|

The M2-Muscarinic Receptor Inhibits the Development of Streptozotocin-Induced Neuropathy in Mouse Urinary Bladder

Abstract: We investigate the role of M 2 -muscarinic receptors in maintaining neurogenic bladder contraction during hyperglycemia. Mice were injected with a single dose of streptozotocin (125 mg/kg), and neurogenic contraction of urinary bladder from wild type and M 2 -muscarinic receptor knockout (M 2 KO) mice was measured at 8 to 24 weeks after treatment. In wild-type bladder lacking urothelium, the summation of the cholinergic (64%) and purinergic (56%) components of the electrical-field-stimulated response exceeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…From this result, we conclude that the M2 muscarinic receptors plays a more important role than the M3 muscarinic receptors after crushing nerve injury, and the role of the M2 or M3 receptor after nerve injury could be different from that of a normal bladder. Consistent with the results from the present study, several studies also have demonstrated that the M2 muscarinic receptors showed the more important role in denervated or hypertrophied bladder contraction [19,20]. Similar with the previous results, M2 muscarinic receptor expression after crushing injury was significantly increased compared with control or sham-operated groups, and this increased expression might be because of compensatory action to maintain bladder contraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From this result, we conclude that the M2 muscarinic receptors plays a more important role than the M3 muscarinic receptors after crushing nerve injury, and the role of the M2 or M3 receptor after nerve injury could be different from that of a normal bladder. Consistent with the results from the present study, several studies also have demonstrated that the M2 muscarinic receptors showed the more important role in denervated or hypertrophied bladder contraction [19,20]. Similar with the previous results, M2 muscarinic receptor expression after crushing injury was significantly increased compared with control or sham-operated groups, and this increased expression might be because of compensatory action to maintain bladder contraction.…”
Section: Discussionsupporting
confidence: 92%
“…A lower midline incision was made and the prostate gland was exposed. After identifying of MPG on the lateral side to bilateral prostates [20], the nerve bundles from the MPG to the bladder were identified and isolated (Figure 6). In sham-operated group, there was no further surgical manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, one of these studies suggested that enhancements may not be detectable at early time points (2 weeks after STZ injection) but only at later ones (8‐9 or 22‐24 weeks), which contrasts the time course of hypertrophy development; moreover, enhancements disappeared when contractions were normalized to those elicited by KCl, but interpretation of this finding is difficult as the KCl responses were not reported . A second report based on the same animals described a reduced contraction to EFS in M 2 receptor knock‐out but not wild‐type mice, which similarly involved the muscarinic and the purinergic component of contraction, pointing to possible compensatory changes in the contributions of M 2 and M 3 receptors.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 99%
“…Later, it was claimed that there was a reduction in the non-cholinergic contractile component of parasympathetic nerve stimulation in 12 weeks STZ-rats, probably caused by a reduction in release of the non-cholinergic transmitter [180]. It was proposed that cholinergic and purinergic parasympathetic nerve components of contraction were minimally affected by STZ treatment, but in M 2 -muscarinic knockout mouse bladder, STZ treatment reduced both the cholinergic and purinergic components [181]. There are conflicting reports about the changes in ATP-mediated neural responses in STZ-diabetic bladder.…”
Section: Purinergic Signalling In Diabetesmentioning
confidence: 99%